The Reconstruction of Mirzo Ulugbek Madrasa Minaret - Muxtarovna, Gafurova (Indonesian Journal Publisher, 2025)
Attention to Islamic architectural monuments built and rebuilt in Turkestan in the early XIX–XX centuries is increasing. Along with the demolition of mosques, madrassahs, tombs, and tombs in the territory of Turkestan at that time, the issue of their preservation was on the agenda. Study, the transfer to the next generations of the scientific and spiritual heritage related to the Islamic religion and its influence on the formation of the architectural culture inherent in the way of life, customs and traditions of the peoples of the world for millennia, is one of the most urgent tasks of today. In this article highlights of the reconstruction of the historical heritage Mirzo Ulugbek madrasa minaret and it’s historical root in the country.